2000
DOI: 10.1002/1097-0223(200007)20:7<552::aid-pd871>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

FISH analysis on day 5 post‐insemination of human arrested and blastocyst stage embryos

Abstract: Preimplantation genetic diagnosis (PGD) is usually performed on cleavage stage embryos on day 3 post‐insemination. Fluorescent in situ hybridization (FISH) has revealed four groups of chromosome patterns in embryos at this stage: uniformly normal, uniformly abnormal, mosaic and chaotic. Recently, some in vitro fertilization (IVF) clinics have started to perform blastocyst stage transfer. In blastocysts, conventional karyotyping has shown that all four groups of chromosome patterns are observed. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
44
3
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 40 publications
8
44
3
1
Order By: Relevance
“…With the establishment of in-vitro systems for culturing mammalian embryos and the availability of probes specific to each human chromosome, the fluorescence in-situ hybridization (FISH) technique has become almost a routine approach to assess human embryos at different stages of development in vitro (Evsikov & Verlinsky 1998, Ruangvutilert et al 2000, Sandalinas et al 2001, Bielanska et al 2005. These studies have demonstrated that, depending on the number and specificity of probes used and the quality of the embryos and/or the patient population examined, the incidence of abnormalities detected varies from 15% to 9 85% (Bielanska et al 2002).…”
Section: Introductionmentioning
confidence: 90%
“…With the establishment of in-vitro systems for culturing mammalian embryos and the availability of probes specific to each human chromosome, the fluorescence in-situ hybridization (FISH) technique has become almost a routine approach to assess human embryos at different stages of development in vitro (Evsikov & Verlinsky 1998, Ruangvutilert et al 2000, Sandalinas et al 2001, Bielanska et al 2005. These studies have demonstrated that, depending on the number and specificity of probes used and the quality of the embryos and/or the patient population examined, the incidence of abnormalities detected varies from 15% to 9 85% (Bielanska et al 2002).…”
Section: Introductionmentioning
confidence: 90%
“…Ay rı ca embri yo la rın ge li şi mi nin dur ma sın dan en faz la ge netik fak tör le rin so rum lu ol du ğu nu bil mek te yiz. 10,49 Ça lış ma mız da sperm FISH ano ma li le ri ile em bri yo can lı lık la rı ara sın da an lam lı bir so nuç el de edi leme miş ol ma sı ne de niy le in ce le di ği miz grup ta tek ba şı na sperm FISH ano ma li le ri nin ye ter li ol ma dı -ğı nı dü şü ne bi li riz. Et ki eden di ğer fak tör le rin araş-tı rıl ma sı için plan la nan ça lış ma la rın, em bri yo canlı lı ğı nı art tır mak için yol gös te ri ci ola ca ğı nı dü şün-mek te yiz.…”
Section: Medical Geneticsunclassified
“…Indeed, a significant feature of preimplantation human development is the intercellular variability within the embryo, with both 'normal' and 'abnormal' cells in close proximity. These abnormal cells have nuclear or chromosomal abnormalities (Hardy et al 1993, Munné et al 1995, Ruangvutilert et al 2000 (Fig. 3), or may have ceased to undergo cell division; all these anomalies probably result from cell cycle defects within individual cells.…”
Section: Human Embryo Development In Vitromentioning
confidence: 99%
“…3), or may have ceased to undergo cell division; all these anomalies probably result from cell cycle defects within individual cells. Such 'mosaicism' is common, with 40 -60% of human embryos consisting of a mixture of healthy and abnormal cells (Hardy et al 1993, Munné et al 1994, Ruangvutilert et al 2000. In addition, cell death is a widespread feature, the majority of human blastocysts having one or more dying cells in both the inner cell mass and the trophectoderm (Hardy 1999) (Fig.…”
Section: Human Embryo Development In Vitromentioning
confidence: 99%